Takhrij and Syarah Hadith of Chemistry: The Law of Treatment with Khamr - Uswatun Hasanah; Alfina Febrianty; Reza Pahlevi Dalimunthe; Solihin Solihin; Rizka Fitriyani S (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the law of treatment with khamr. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this research is that khamr is not only in the form of a drink but everything that makes you lose your mind. The conclusion of this research is takhrij and syarah hadith of the Prophet regarding the law, treatment with khamr is haram, but when in a state of extreme emergency it is permissible in moderation.